STUDY OF LAND COVER AND BIODIVERSITY IN RELATION TO ROAD DEVELOPMENT IN MUARA KAMAN SEDULANG NATURE RESERVE - Apansyah, Apansyah; Kristiningrum, Rochadi Kristiningrum; Aipassa, Marlon Ivanhoe; Pardosi, Jawatir; Sarwono, Edhi; Duakaju, Nella Naomi (Universitas Gorontalo, 2024)
This study evaluates the environmental impact of road construction in the Muara Kaman Sedulang Nature Reserve (CAMKS), with a particular focus on land cover changes and biodiversity loss. The 8.189 km road construction aims to connect the isolated areas between Kupang Baru Village and Liang Buaya Village. Satellite imagery was used to analyze land cover changes due to road construction, while field surveys were conducted to assess the biodiversity of flora and fauna affected by the development. Findings research indicate thatÂ majority of land covers consist of shrub/swamp thicket. Additionally, no protected plant species were found in either village, but naturally growing tree species were identified, and approximately 26% of protected wildlife were located within the CAMKS area. This means the impacts include habitat loss, disruption of natural behaviors, and increased risk of vehicle-related fatalities, and that the area holds high conservation value.